2003
DOI: 10.1039/b209165h
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3-phenylprop-2-ynylamines as inhibitors of mammalian squalene epoxidaseElectronic supplementary information (ESI) available: Proton NMR spectra for the intermediate piperidines 56–60 and acetylenes 63-81 and 85,86. See http://www.rsc.org/suppdata/ob/b2/b209165h/

Abstract: The synthesis of a novel series of 3-phenylprop-2-ynylamines as selective mammalian squalene epoxidase inhibitors is described. Structure activity relationship studies led to the discovery of compound 19, 1-[3-(3,5-dichlorophenyl)-prop-2-ynyl]-3- methylpiperidine hydrochloride with an IC50 of 2.8 +/- 0.6 microM against rat liver squalene epoxidase. Against 23 strains of fungal squalene epoxidase compound 19 was found to be inactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…CTB(H,C 2 H) was obtained in two steps in 80 % overall yield from CTB(H,OTf) [56] by Sonogashira cross‐coupling with trimethysilylacetylene using [Pd(PPh 3 ) 2 Cl 2 ] as catalyst and Et 3 N as base, followed by removal of the TMS protecting groups with tetrabutylammonium fluoride [66] . The trinuclear gold complexes CTB(H,C 2 AuPR 3 ) (R=Ph: 1 ; R=Et: 2 , and R=Cy: 3 ), were prepared by nucleophilic substitution of [Au(PR 3 )Cl] (R=Ph, Et, and Cy) in the presence of sodium methoxide [67,68] .…”
Section: Resultsmentioning
confidence: 99%
“…CTB(H,C 2 H) was obtained in two steps in 80 % overall yield from CTB(H,OTf) [56] by Sonogashira cross‐coupling with trimethysilylacetylene using [Pd(PPh 3 ) 2 Cl 2 ] as catalyst and Et 3 N as base, followed by removal of the TMS protecting groups with tetrabutylammonium fluoride [66] . The trinuclear gold complexes CTB(H,C 2 AuPR 3 ) (R=Ph: 1 ; R=Et: 2 , and R=Cy: 3 ), were prepared by nucleophilic substitution of [Au(PR 3 )Cl] (R=Ph, Et, and Cy) in the presence of sodium methoxide [67,68] .…”
Section: Resultsmentioning
confidence: 99%
“…The nitro group in the coupled product, 51 , was then transformed to the bromo group by reduction to the amine and diazotization under hydrophobic conditions using tert -butyl nitrite in the presence of cupric bromide . Aryl bromide 53 underwent Sonagashira coupling with trimethylsilylacetylene to give the protected phenylacetylene 54 . Desilylation of 54 with tetra( n -butyl)ammonium fluoride 52 provided phenylacetylene 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Then we came to the final stage of the synthesis of key segment 4 : Sonogashira coupling between sulfonic ester 13 and (triisopropylsilyl)­acetylene. Initially, we applied the reaction conditions reported in the literature which yielded desired product 14 with a conversion rate of less than 50% . After a few attempts, we found that a phase transfer catalyst (TBAB) could shorten the reaction time obviously and achieve complete conversion .…”
mentioning
confidence: 99%
“…Initially, we applied the reaction conditions reported in the literature which yielded desired product 14 with a conversion rate of less than 50%. 14 After a few attempts, we found that a phase transfer catalyst (TBAB) could shorten the reaction time obviously and achieve complete conversion. 15 Finally, deprotection of silyl ether 14 proceeded smoothly to afford key segment phenylacetylene 4.…”
mentioning
confidence: 99%